A Tale of Old and Young Volcanoes in Monts d'Ardèche UNESCO Global Geopark (South-Eastern France) - Jean-Paul Raynal; Emmanuelle DEFIVE; Nicolas Klee; Roxane Buso; Didier Laporte (Geoconservation Research)
The Regional Natural Park of the Monts d'Ardèche, located in south-eastern France, became the Monts d’Ardèche UNESCO Global Geopark in September 2014. This territory possesses significant volcanic features dating from the Miocene to the late Pleistocene. The UNESCO Global Geopark label helped to formalize a long-standing partnership with the University of Clermont Auvergne which includes support for scientific research, establishing conservation and protection priorities, establishing geosites for the public and involvement of local people and communities in geotouristic initiatives. Here we focus on some peculiar geosites that allow us to question magmatic processes, eruptive dynamics, morphological evolution of landscapes, the chronology of eruptions, relationships between humans and volcanoes during the Pleistocene, and highlight the delicate alliance between economic pressures, heritage conservation, and scientific tourism.